Family-Based Reproductive Health Education as a Strategy to Prevent Child Marriage: A Literature Review of Its Impact on Adolescents’ Knowledge and Attitudes - Nurannisa Fitria Aprianti; Eka Faizaturrahmi; Baiq Dika Fatmasari (Bulletin of Inspiring Developments and Achievements in Midwifery, 2024)
Child marriage persists as a major public health and human rights issue, especially in low- and middle-income countries where poor reproductive health literacy and weak family involvement heighten adolescents' risks. While family-based approaches to sexual and reproductive health (SRH) education are gaining traction, evidence on their effects on adolescents' knowledge and attitudes toward preventing child marriage remains unsynthesized. This study synthesizes recent empirical evidence (2021–2024) on family-based SRH education's impact on these outcomes. Using a literature review, we analyzed 15 peer-reviewed articles from Asian and African contexts, focusing on adolescents aged 10–19 and their parents/caregivers. Studies spanned randomized controlled trials, quasi-experimental, cross-sectional, mixed-methods, and qualitative designs, evaluating intervention features, family communication, strategies, and outcomes like knowledge and attitudes. Results show structured family interventions—with open, dialogic communication, parental training, culturally tailored materials, and interactive/digital media—markedly boost adolescents' SRH literacy and promote attitudes favoring marriage delay. Barriers included unidirectional communication and low parental capacity. These insights underscore the need for parental empowerment and multisectoral partnerships in policies. Family-based SRH education offers an evidence-based strategy to combat child marriage. Future studies should emphasize longitudinal, culturally adaptive models for greater sustainability and relevance.